The Influence of Good Corporate Governance and Stakeholder Pressure on the Quality of Sustainability Report Disclosures - Harsono, Khaerunisa; Sari, Prima Yusi; Rosdini, Dini (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2024)
Economic recovery after the Covid-19 pandemic must prioritize sustainability. The current government continues to make the economy run together with many parties (Kontan, 2020). As a result of the COVID-19 pandemic, 2020 has been marked as a turning point in environmental, social, and governance (ESG) investment due to ongoing global challenges. Due to the higher tension of climate change issues and the current socio-political environment, more businesses are encouraged to embrace a commitment to the ESG (environmental, social, and governance) framework. The population in this study are companies listed on the Indonesia Stock Exchange (IDX) and in the energy, raw materials, industry, and infrastructure sectors and issuing sustainability reports during the period 2015 - 2020. The company's annual report data is obtained from the publication on the website of the Indonesia Stock Exchange (IDX). Media exposure Data obtained by online newspaper media. Good Corporate governance and stakeholder pressure (shareholders, employees, government, and media) significantly influence the disclosure of Sustainability reports in the energy, raw goods, industrial, and infrastructure sector companies in the 2015-2020 period. However, the study found that stakeholder pressure from employees had a significant negative impact on the disclosure of the Sustainability Report. This result shows that, decreasing the number of employees can increase the disclosure of Sustainability Report. Because, for most employees, the disclosure of the Sustainability Report has no effect if there is no direct impact felt by the employee.